2013
DOI: 10.1186/2042-6410-4-19
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in the expression of lupus-associated miRNAs in splenocytes from lupus-prone NZB/WF1 mice

Abstract: BackgroundA majority of autoimmune diseases, including systemic lupus erythematosus (SLE), occur predominantly in females. Recent studies have identified specific dysregulated microRNAs (miRNAs) in both human and murine lupus, implying an important contribution of these miRNAs to lupus pathogenesis. However, to date, there is no study that examined sex differences in miRNA expression in immune cells as a plausible basis for sex differences in autoimmune disease. This study addresses this aspect in NZB/WF1 mice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
57
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(60 citation statements)
references
References 49 publications
3
57
0
Order By: Relevance
“…similarly, before the onset of sle, the two genders do not differ in their expression of mirs (mir-182-96-183, mir-31 and mir-148a, mir-155) except mir-127 and mir-379. after sle onset, however, the levels of mir-182-96-183, mir-31, mir-127, mir-379 and mir-148a are elevated in 30 weeks old females compared to age-matched males without sle features 84 . Furthermore, estrogen-treated orchiectomized 32 weeks old mice express similar levels of these mirs as their female counterparts 84 .…”
Section: Mirs and Hormonal Influences In Slementioning
confidence: 79%
See 2 more Smart Citations
“…similarly, before the onset of sle, the two genders do not differ in their expression of mirs (mir-182-96-183, mir-31 and mir-148a, mir-155) except mir-127 and mir-379. after sle onset, however, the levels of mir-182-96-183, mir-31, mir-127, mir-379 and mir-148a are elevated in 30 weeks old females compared to age-matched males without sle features 84 . Furthermore, estrogen-treated orchiectomized 32 weeks old mice express similar levels of these mirs as their female counterparts 84 .…”
Section: Mirs and Hormonal Influences In Slementioning
confidence: 79%
“…after sle onset, however, the levels of mir-182-96-183, mir-31, mir-127, mir-379 and mir-148a are elevated in 30 weeks old females compared to age-matched males without sle features 84 . Furthermore, estrogen-treated orchiectomized 32 weeks old mice express similar levels of these mirs as their female counterparts 84 . all these data explain the modulation of mirs by estrogen and support selected mirs as mediators of the alteration of immune reactions to autoimmunity by sex hormones.…”
Section: Mirs and Hormonal Influences In Slementioning
confidence: 79%
See 1 more Smart Citation
“…In addition, activated ERα attenuates the processing of specific primary miRNAs into pre-miRNAs through estrogen-dependent association with the Drosha complex, resulting in an increased stabilization of the miRNA-targeting transcript. This suggests that estrogen can post-transcriptionally control gene expression through regulation of the miRNAs, which target the 3′UTRs of these genes (120, 121). …”
Section: Environmental and Hormonal Regulation Of Mirnas In Lupusmentioning
confidence: 99%
“…Numerous dysregulated miRNAs have been identified in both human and murine lupus, thereby implicating their role in lupus pathogenesis 13,17,19. To determine the contribution of sexually dimorphic miRNA expression to the sex bias of autoimmune disease, we recently investigated the sex differences in the expression of lupus-associated miRNAs, including the miR-182-96-183 cluster, miR-155, miR-31, miR-148a, miR-127, and miR-379, in splenocytes of male and female NZB/W F1 mice 16,22. We found that the sex differences in the expression of aforementioned lupus-associated miRNAs were markedly evident after the onset of lupus, especially at 30 weeks of age when female NZB/W F1 mice manifested moderate to severe lupus.…”
Section: Sexually Dimorphic Mirna Expression In Immune Cells In the Cmentioning
confidence: 99%